2014
DOI: 10.1158/1055-9965.epi-13-0747
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acculturation, Nativity, and Years Living in the United States with Biobanking among Individuals of Mexican Descent

Abstract: Background Biobanking is the collection of human biospecimens (tissues, blood and body fluids) and their associated clinical and outcome data. Hispanics are less likely to provide biological specimens for biobanking. The purpose of this study was to investigate the association of acculturation, nativity status and years living in the United States with participation in biobanking among individuals of Mexican descent. Methods Participants were 19,212 adults of Mexican descent enrolled in an ongoing population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…As observed in studies with other Hispanic sub-groups, Mexican-Americans in our study expressed an interest in donating biospecimens to a biobank [8,20] and were willing to do so to help advance scientific research or for other altruistic reasons, such as potentially benefiting family in the future [10,12-16,21]. Studies with other racial/ethnic minority groups, such as African Americans, Vietnamese and Chinese individuals [10,13,14,21] as well as Non-Hispanic Whites [22] also found that the desire to help future generations and to contribute to science was a motivator for participating in biobanking.…”
Section: Discussionsupporting
confidence: 52%
“…As observed in studies with other Hispanic sub-groups, Mexican-Americans in our study expressed an interest in donating biospecimens to a biobank [8,20] and were willing to do so to help advance scientific research or for other altruistic reasons, such as potentially benefiting family in the future [10,12-16,21]. Studies with other racial/ethnic minority groups, such as African Americans, Vietnamese and Chinese individuals [10,13,14,21] as well as Non-Hispanic Whites [22] also found that the desire to help future generations and to contribute to science was a motivator for participating in biobanking.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, findings from a survey of repository facilities, in the Midwest and Northwest USA, indicated that only 1.3 % of collected biospecimens were from Hispanic participants, compared to 89 % of biospecimens from White participants, and that about half of the surveyed facilities had made efforts to collect biospecimens in their communities (Simon et al 2014). There is an expanding body of literature that documents the significant efforts to engage ethnically and racially diverse communities in biospecimen research across the US (Braun et al 2014;Cohn et al 2014;Dang et al 2014;Dash et al 2014;Erwin et al 2013;Lopez et al 2014;Luque et al 2012;Rodriguez et al 2013). To date, only a few studies have explored biobanking awareness, perceptions, beliefs (Hohl et al 2014;Luque et al 2012;Rodriguez et al 2013), willingness to donate biospecimens (Hohl et al 2014;Lopez et al 2014), and attitudes toward biobanking (Hohl et al 2014) among Hispanic populations in the US.…”
Section: Introductionmentioning
confidence: 99%
“…There is an expanding body of literature that documents the significant efforts to engage ethnically and racially diverse communities in biospecimen research across the US (Braun et al 2014;Cohn et al 2014;Dang et al 2014;Dash et al 2014;Erwin et al 2013;Lopez et al 2014;Luque et al 2012;Rodriguez et al 2013). To date, only a few studies have explored biobanking awareness, perceptions, beliefs (Hohl et al 2014;Luque et al 2012;Rodriguez et al 2013), willingness to donate biospecimens (Hohl et al 2014;Lopez et al 2014), and attitudes toward biobanking (Hohl et al 2014) among Hispanic populations in the US. Two of these qualitative studies found low awareness of biobanking initiatives and uncertainty about the process (Luque et al 2012;Rodriguez et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10,15 Studies examining the effect of acculturation, including the number of years lived in the United States, place of birth, and English-speaking proficiency, and healthcare access and barriers on willingness to donate blood for research in other minority groups, have had conflicting results. [15][16][17] While prior studies have examined participants' motivation to contribute to biospecimen research, [8][9][10] there has not been a thorough examination of this motivation with respect to individuals of Korean descent. The purpose of this study is to examine attitudes toward biospecimen research as a mediator of the relationship between demographic and healthcare access factors and willingness to donate blood for the purpose of research among individuals of Korean heritage.…”
mentioning
confidence: 99%